2006
DOI: 10.1111/j.1572-0241.2006.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Markers of Liver Fibrosis and Inflammation in Chronic Hepatitis B-Virus Related Liver Disease

Abstract: Significant hepatic fibrosis and necroinflammation can reliably be predicted using routinely checked tests and HBV DNA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 26 publications
7
79
0
1
Order By: Relevance
“…These tests, called multianalyte assays with algorithmic analyses (MAAAs), based on correlating and normalizing multiple sets of variables, are increasing in usage and show applicability in many diseases. FibroSure (FibroTest), for example, is a six-panel blood test for liver damage which has become widely used for hepatitis C diagnosis and detection and can replace liver biopsy [33,34]. MammaPrint, a 70-gene assay test for metastatic breast cancer, was FDA approved in 2007.…”
Section: Multianalyte Assays With Algorithm Analysesmentioning
confidence: 99%
“…These tests, called multianalyte assays with algorithmic analyses (MAAAs), based on correlating and normalizing multiple sets of variables, are increasing in usage and show applicability in many diseases. FibroSure (FibroTest), for example, is a six-panel blood test for liver damage which has become widely used for hepatitis C diagnosis and detection and can replace liver biopsy [33,34]. MammaPrint, a 70-gene assay test for metastatic breast cancer, was FDA approved in 2007.…”
Section: Multianalyte Assays With Algorithm Analysesmentioning
confidence: 99%
“…Liver biopsy is considered to be a gold standard to establish the precise diagnosis of liver cirrhosis. However, it is an invasive procedure, and small biopsies are more prone to sampling error [19,20]. Although all of the cases in our studies were confirmed by liver biopsy, it was very difficult to repeat the liver biopsy for follow up in these patients.…”
Section: Discussionmentioning
confidence: 64%
“…Assessment of liver fibrosis with multiple serum markers used in combination is sensitive, specific, and reproducible, suggesting that multiple serum markers may be used in conjunction with liver biopsy to assess a range of chronic liver diseases. Recently, algorithms and indices using clinical and biochemical measurements have been advanced as methods for detecting liver fibrosis in chronic hepatitis C [9,12,14,15,18], and current noninvasive scores give reliable information on liver fibrosis in one-third of patients with chronic hepatitis C, especially when used in combination; however, there are insufficient reports in patients with chronic hepatitis B [13,17,19].…”
Section: Introductionmentioning
confidence: 99%